2012
DOI: 10.5047/eps.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The Gyra washover fan in the Lefkada Lagoon, NW Greece—possible evidence of the 365 AD Crete earthquake and tsunami

Abstract: Coastal geomorphological and geological archives store valuable information about the geodynamic evolution of coastal areas and the contributing geomorphodynamic processes. The coastal geomorphology of the LefkadaPreveza coastal zone, NW Greece, holds evidence for the influence of both gradual, low-energy and episodic, high-energy coastal processes. Situated close to the Hellenic Arc and the Cefalonia transform fault, the area belongs to one of the seismically most active regions in the Mediterranean. Thus, ts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Lagoons, small lakes and saltpans: Lefkas lagoon (L03) is the largest lagoon of the Ionian Islands (Figure 5d,e), separated from the Ionian Sea by the narrow sandy Gyra spit (L02), which is a large sandy barrier landform in the northernmost part of Lefkas (Figure 6a,b), ranging from the area of Gyra to Aghios Ioannis (Figures 2 and 4). The sediment of the sand strip comes mainly from landslides due to earthquakes on the west coast of the island [90,91] (May et al, 2012a,b), while white and coarse beachrocks can be found at the mean sea-level, along the strip's coastline ( [91] and own observations). Moreover, palaeo-tsunami deposits have been located, probably associated with the 365 A.D. earthquake in Crete [91][92][93].…”
Section: Lefkas Islandmentioning
confidence: 99%
“…Lagoons, small lakes and saltpans: Lefkas lagoon (L03) is the largest lagoon of the Ionian Islands (Figure 5d,e), separated from the Ionian Sea by the narrow sandy Gyra spit (L02), which is a large sandy barrier landform in the northernmost part of Lefkas (Figure 6a,b), ranging from the area of Gyra to Aghios Ioannis (Figures 2 and 4). The sediment of the sand strip comes mainly from landslides due to earthquakes on the west coast of the island [90,91] (May et al, 2012a,b), while white and coarse beachrocks can be found at the mean sea-level, along the strip's coastline ( [91] and own observations). Moreover, palaeo-tsunami deposits have been located, probably associated with the 365 A.D. earthquake in Crete [91][92][93].…”
Section: Lefkas Islandmentioning
confidence: 99%
“…Thus, the region is characterized by a high seismic and tsunami hazard risk (Papazachos & Dimitriu, ). In fact, numerous historical accounts (Soloviev et al ., ), as well as detailed sedimentary studies indicate repeated tsunami landfall in western Greece (Scheffers et al ., ; Vött et al ., ; May et al ., ). However, Marriner et al .…”
Section: Study Areamentioning
confidence: 76%
“…Thus, the region is characterized by a high seismic and tsunami hazard risk (Papazachos & Dimitriu, 1991). In fact, numerous historical accounts (Soloviev et al, 2000), as well as detailed sedimentary studies indicate repeated tsunami landfall in western Greece (Scheffers et al, 2008;V€ ott et al, 2010;May et al, 2012). However, Marriner et al (2017), using statistical analysis, suggested that repeated cycles of strong storms could be an alternative cause for boulder movement.…”
Section: Western Greecementioning
confidence: 99%
“…The associated tsunami devastated coasts and man-made coastal infrastructure between the Levante and Italy as documented by geological evidence (e.g. De Martini et al 2010, Gerardi et al 2012, Smedile et al 2011, 2012, May et al 2012, Ntageretzis et al 2015, Polonia et al 2013, Finkler et al 2018. Impacted regions are located up to 500-600 km distant from the suggested tsunamigenic fault.…”
Section: Synthesis Of Archaeological and Geoarchaeological Datamentioning
confidence: 99%